Variability of selected indicators of physical activity in a randomized sample of the Czech population between the years 2003-2006: Results from the short and long self administered format of the IPAQ questionnaire [Variabilita vybraných indikátorů pohybové aktivity u randomizovaných souborů české populace v letech 2003-2006: Výsledky z krátké a dlouhé administrativní verze IPAQ dotazníku] - Erik Sigmund; Dagmar Sigmundová; Josef Mitáš; František Chmelík; Jana Vašíčková; Karel Frömel (Palacky University, 2009)
BACKGROUND: The effort to gain worldwide data on the levels of physical activity (PA) of different populations, which would be comparable, led to the creation and standardization of the International Physical Activity Questionnaire (IPAQ). OBJECTIVE: The main goal of this study is to determine the variability of PA indicators of two equivalent forms of the Czech self administered format of the IPAQ questionnaire applied in a randomized sample of the Czech population between the years 2003-2006. METHODS: A randomized sample of 11277 (5683 females and 5594 males) of the Czech population aged 15-69 took part in the study. The short self administered format of the IPAQ was applied in 2066 women and 1976 men in Fall 2003 and Spring 2004. The long self administered format of the IPAQ (or as a part of the ANEWS questionnaire) was applied to 1688 women and 1689 men in Fall 2004 and Spring 2005 (or in 1929 women and 1929 men in Fall 2005 and Spring 2006). Individual samples of respondents were randomized according to sex, age, and size of the location of residence in compliance with the data from the Czech Statistical Office (www.czso.cz). RESULTS: There are no significant differences found between men and women in MET-minutes/week in total PA, transportation PA, job related PA and walking as shown by the separately applied long self administered format of the IPAQ and the ANEWS questionnaire (inc. long format of IPAQ). In the self administered format of the IPAQ, we have found both in men and women lower values of total PA (p < 0.0001) than in the long self administered format of the IPAQ or the ANEWS questionnaire. No differences between the values of MET-minutes/week for walking and sitting both in men and women on working days were found in the different forms of the IPAQ questionnaire. CONCLUSIONS: Having used the equivalent forms of the short or long Czech self administered format of the IPAQ questionnaire, we have not found any differences between MET-minutes/week for walking and sitting on working days. The long self administered format of the IPAQ provides more detailed results on PA. However, the value of total PA is significantly higher than that obtained using the short self administered format of the IPAQ. In order to obtain more exact data on PA, we recommend using the long self administered format of the IPAQ simultaneously with pedometer or accelerometer PA monitoring. [VÝCHODISKA: Snaha o získání celosvětově srovnatelných výsledků o úrovni pohybové aktivity (PA) různých populačních skupin vyústila ve vytvoření a standardizaci Mezinárodního dotazníku o pohybové aktivitě (IPAQ). CÍLE: Hlavním cílem této studie bylo zjistit variabilitu vybraných proměnných PA ze dvou ekvivalentních forem českých administrativních verzí IPAQ dotazníku aplikovaných u randomizovaných souborů české populace v letech 2003-2006. METODIKA: Ve studii byla použita data od 11277 obyvatel České republiky (5683 žen a 5594 mužů) ve věku 15-69 let. Krátká administrativní verze IPAQ byla u 2066 žen a 1976 mužů aplikována na podzim 2003 a jaře 2004. Dlouhá administrativní verze IPAQ (resp. jako součást ANEWS dotazníku) byla použita u 1688 žen a 1689 mužů na podzim 2004 a jaře 2005 (resp. u 1929 žen a 1929 mužů na podzim 2005 a jaře 2006). Jednotlivé soubory účastníků byly randomizovány podle pohlaví, věku a velikosti místa bydliště v souladu s údaji Českého statistického úřadu (www.czso.cz). VÝSLEDKY: Mezi samostatně aplikovanou dlouhou verzí IPAQ a ANEWS dotazníkem (obsahujícím dlouhou verzi IPAQ) nenacházíme u mužů ani žen výrazné rozdíly v MET-minut/týden v celkové PA, transportní PA, PA v zaměstnání a chůzi. U krátké verze IPAQ zaznamenáváme u mužů i žen nižší hodnoty celkové PA (p < 0,0001) než v dlouhé verzi IPAQ (resp. ANEWS dotazníku). Bez rozdílu mezi jednotlivými ekvivalentními formami IPAQ dotazníku jsou u mužů i žen hodnoty MET-minut/týden za chůzi a doba sezení v pracovních dnech. ZÁVĚRY: Při použití ekvivalentních administrativních verzí IPAQ dotazníku nezjistíme rozdílné hodnoty u MET-minut/týden za chůzi a denní doby sezení. Dlouhá administrativní verze IPAQ podává detailnější výsledky o PA, avšak její celková hodnota je významně vyšší než při použití krátké verze IPAQ. Pro přesnější zjišťování PA doporučujeme souběžné používání dlouhé administrativní verze IPAQ s přístrojovým monitorováním, alespoň pomocí pedometru, lépe však pomocí akcelerometru.]